Comparative Analysis of Approaches to Assess the Quality of Inactivated Influenza Vaccines: Regulatory Requirements in the Russian Federation and European Union - L. M. Khantimirova; S. G. Guseva; V. A. Shevtsov; V. A. Merkulov; V. P. Bondarev (Эпидемиология и вакцинопрофилактика, 2021)
The experience with the influenza pandemic caused by strain A (H1N1) 2009 and the existing gaps in standardizing and evaluating the quality and effectiveness of vaccines for influenza prevention have led the European Union (EU) to recognize the need to review / update the current guidelines on requirements for the development, quality, and preclinical and clinical research. In February 2018 Guideline on influenza vaccines -quality module (EMA/CHMP/BWP/310834/2012 Rev.l) came Into effect In the EU countries. The formation of the Eurasian Economic Union (EAEU) and the creation of a single market for pharmaceutical products entails the need to amend the current and the formation of new legislation, as well as changes in the rules and regulations regarding the pharmaceutical circulation processes in the Russian Federation: development, quality assurance in preclinical and clinical trials, monitoring the safety of medicines for medical use, in this regard, it seems appropriate to develop scientific and technical guidelines that are harmonized with international standards and approaches in the pharmaceutical field. The aim of the review was to conduct a comparative analysis of approaches to assessing the quality of vaccines for prevention influenza based regulatory requirements in the Russian Federation and European Union. Conclusion. In this article discusses the features of the requirements for the development and quality control of inactivated influenza vaccines in the Russian Federation and the EU. The article provides a comparative analysis of the requirements of the State Pharmacopoeia of the Russian Federation and the European Pharmacopoeia for quality indicators, which should be included in the regulatory documentation when registering the vaccine. The main changes in the EMA document «Guidelines for influenza vaccines - Quality module» consist of new approaches to standardizing vaccines for influenza prevention, in particular, determining the specific activity of inactivated influenza vaccines using adequate alternative methods and studying biological, immunological and physicochemical characteristics HA antigen using a wide range method. The results of the analysis of approaches to assessing the quality of vaccines for influenza prevention can be useful in developing harmonized with international norms and approaches scientific and technical guidelines in the pharmaceutical field.